2012
DOI: 10.1530/rep-12-0113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial DNA accumulation during oocyte growth and meiotic maturation in the mouse

Abstract: Oocytes accumulate an enormous quantity of mitochondrial (mt) DNA, and an insufficient amount of mtDNA may underlie some cases of poor oocyte quality leading to infertility. Little is known, however, about the mechanisms that govern the timing and regulation of mtDNA accumulation during oogenesis. We report, through analysis of the mtDNA content of individual oocytes of the mouse, that mtDNA accumulates steadily during oocyte growth to reach a value of w175 000 copies per cell. MtDNA content ceases to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 36 publications
2
23
1
2
Order By: Relevance
“…A similar general trend was observed for all target genes examined and may explain, in part, why mtDNA copy numbers have been reported not to increase during IVM of equine oocytes (Rambags et al 2014). A decrease in relative gene expression for TFAM and mtPOLB after oocyte maturation has previously been reported for porcine and murine oocytes Mahrous et al 2012) and related to the arrest in mitochondrial replication that is observed during early embryonic development. However, the absolute reduction in mtDNA copy number in oocytes of mares $12 years after IVM observed by Rambags et al (2014) was thought to be a factor of mitochondrial deterioration, as indicated by electron microscopic evidence of mitochondrial swelling and disintegration.…”
Section: Discussionsupporting
confidence: 83%
“…A similar general trend was observed for all target genes examined and may explain, in part, why mtDNA copy numbers have been reported not to increase during IVM of equine oocytes (Rambags et al 2014). A decrease in relative gene expression for TFAM and mtPOLB after oocyte maturation has previously been reported for porcine and murine oocytes Mahrous et al 2012) and related to the arrest in mitochondrial replication that is observed during early embryonic development. However, the absolute reduction in mtDNA copy number in oocytes of mares $12 years after IVM observed by Rambags et al (2014) was thought to be a factor of mitochondrial deterioration, as indicated by electron microscopic evidence of mitochondrial swelling and disintegration.…”
Section: Discussionsupporting
confidence: 83%
“…Mahrous et al (2012) suggested that the Mt number in mouse oocytes remains constant once the oocytes reach full size. By contrast, the Mt number in porcine oocytes was found to increase during maturation period (Mao et al 2012, Pawlak et al 2012.…”
Section: Mitochondrial Impairments and Kineticsmentioning
confidence: 99%
“…Early embryonic development may be supported by whole, already existing mitochondria without de novo synthesis (Wai et al 2010), although a few studies suggest that de novo mitochondrial synthesis occurs during early embryonic development (Chiaratti et al 2010). Furthermore, it has been suggested that once mitochondrial number reaches a certain threshold during oocyte maturation, this number is maintained (Mahrous et al 2012, Cotterill et al 2013), but Mao et al (2012) reported that mitochondrial synthesis is induced by supplementation of maturation medium with follicular fluid (FF) and neuregulin 1. Despite the presence of both de novo synthesis and degradation pathways in somatic cells, mitochondrial turnover during oocyte maturation has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increase in the amount of mitochondrial DNA during meiosis I (Mahrous et al, 2012). In these oocytes, mitochondrial numbers reach over 100,000 per cell before the completion of meiosis II.…”
Section: Mitochondria Fusion and Fission During Mitosis And Meiosismentioning
confidence: 99%
“…During the progression from immature to mature embryo sac in P. zonale , over a 900 fold increase in the amount of mitochondrial DNA is observed (Kuroiwa et al, 1996). This increase is mirrored in mouse oocytes, but estimates place the increase to be only 100-fold (Mahrous et al, 2012). These studies of pollen and megaspore development show that the mitochondria change shape, size, and cellular location during meiosis; yet linking these observations to the nuclear genes identified in Arabidopsis with a role in mitochondrial dynamics has not been established.…”
Section: Mitochondria Fusion and Fission During Mitosis And Meiosismentioning
confidence: 99%